Pencatatan Laporan Keuangan Sesuai Dengan PSAK Pada Perusahaan PT. Gio Dipa Energi - Utami, Laras Bela (Universitas Dehasen Bengkulu, 2023)
Financial statements are a means of communicating the main financial information to parties in need, both internal and external to the company, which contains the results of the accounting process that can be used as a means of communicating between financial data and or activities of a company and parties with an interest in the data or activities of a company. in this case, the company PT Gio dipa energy as an entity that issues financial statements for general purposes for external users is expected to study the recording of financial statements in accordance with the standards, namely PSAK standards. the purpose of this study is to determine the recording of financial statements in accordance with the standards. the purpose of this study is to determine the recording of financial statements carried out by PT.gio dipa energy, as well as the obstacles faced in its application. this study uses qualitative research with a case study method. the steps taken to obtain data and information are interviews and documentation. the results in this study indicate that the financial statements prepared by PT Gio dipa energy have implemented PSAK.